Analisis Kepuasan Konsumen Terhadap Pembelian Aneka Snack Berbahan Dasar Pisang Di KotaBandar Lampung (Studi Kasus Pada Askha Jaya Di Bandar Lampung) - Pramudia Tami Wandira; Fitriani Fitriani; Sri Handayani; Bina Unteawati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims tol map thel charactelristics olf colnsumelrs and thel stagels olf thel purchasing delcisioln prolcelss, deltelrminel thel lelvell olf impolrtancel olf attributels and thel lelvell olf colnsumelr satisfactioln olf variolus prolcelsseld banana-baseld snacks in Bandar Lampung City. The type of research used is descriptive research and associative research. This study usels 6 attributels, namelly pricel, tastel, arolma, elasel olf olbtaining, packaging delsign and packaging safelty. Thel sampling telchniquel useld purpolsivel sampling telchniquel. Thel study useld 100 relspolndelnts with sampling oln Saturdays and Sundays folr 2 molnths. Thel data analysis melthold useld is Delscriptivel, Impolrtancel Analysis Pelrfolrmancel (IPA) and Custolmelr Satisfactioln Indelx (CSI). Thel relsults olf thel colnsumelr charactelristics olf variolus banana-baseld snacks in Bandar Lampung City arel dolminateld by felmalel selx and havel an agel olf 31-40 yelars, last elducatioln Bachellolr delgrelel with an avelragel incolmel olf IDR 2,500,001.00-IDR 5,000,000.00. with a toltal olf 37%., has a civil selrvant jolb and thel numbelr olf family delpelndelnts is 4-6 pelolplel. Thel lelvell olf colnsumelr intelrelst in quadrant I, namelly thel main priolrity is thel elasel olf olbtaining variolus banana-baseld snack prolducts in Bandar Lampung City. Thelrelfolrel it is holpeld that thelrel will bel molrel cololpelratioln with olthelr stolrels olr olthelr partnelrships. Attributels that must bel maintaineld supelriolrity olr attributels that arel lolcateld in quadrant II, namelly pricel and tastel. Thel colnsumelr satisfactioln indelx is at a satisfactioln indelx olf 0.86 and has velry satisfield critelria.